Sub-6 GHz Millimeter-Wave Metamaterial Antenna with Reconfigurable Radiation Patterns for Enhanced Wireless Communication - Abubakar LAWAL; Abdulkadir O. ABDULBAKI; Nathaniel SALAWU; Bala A. SALIHU; Mamman A. THOMAS; Abraham U. USMAN (FUDMA Journal of Engineering and Technology, 2025)
6G has been envisioned to utilize the upper mmWave (90-300 GHz) and Terahertz bands (0.1-10 THz). At such high frequencies, high path loss and atmospheric absorption are critical challenges. A highly directional and reconfigurable antenna is required to mitigate these challenges. This research presents a novel, pattern-reconfigurable metamaterial-based antenna for sub-6 GHz mmWave applications. The antenna is based on a graphene metasurface loaded with a novel square-spherical split ring resonator, positioned above a rectangular microstrip patch antenna to provide absorption of unwanted signals and improve gain and spectral efficiency. Placed under the patch is Rogers 5800 substrate with permittivity (ε) of 2.0 and thickness of 0.1mm. The antenna operates between 90-120 GHz, spanning the 102-109 GHz, adopted at the World Radio Congress 2023 for advanced use cases of 6G, and was simulated using the CST suite. The main beam is pattern-reconfigured by two bipolar junction diodes (d1, d2) embedded on the patch antenna. The diodes reconfigure the radiation pattern and affect the S11 reflection coefficient. Specifically, d1 switches between 90-98 GHz, obtaining a minimum S11 of -70.7 dB at 97.5 GHz, while d2 switches between 98-120 GHz, realizing a minimum S11 of -69.6 dB at 105.4 GHz. When fully loaded, a -64.5 dB was obtained, better than similar work compared. These S11 values indicate exceptional impedance matching and minimal signal reflection. The proposed antenna introduces a novel design that integrates a square-spherical split ring resonator with a graphene metasurface, achieving dynamic pattern reconfigurability and deep S11 nulls in a compact structure. The antenna is compact, has a wide bandwidth, and can perform efficiently in 6G use cases, including holographic presence, and smart transport, among others require high radiation efficiency. Real-world use cases include holographic presence, smart mobility, and on-chip THz systems, where beam reconfigurability and low reflection loss are critical.
Keywords: 6G Antenna, Metamaterial, mmWave, Terahertz band, split ring.